Organic sulfur was integral to the Archean sulfur cycle - Mojtaba Fakhraee (Nature Portfolio, 2019)
Marine chemistry during the Early Earth (over 2.7 billion years ago) is commonly inferred to have been inorganically sulfate-reducing. Here, the authors argue that organic sulfur cycling may have played a previously unrecognized, yet important, role in the formation of ancient Archean marine sulfides.